MODELO PARA SUPORTE À GESTÃO ORGANIZACIONAL FUNDAMENTADO NOS PRÊMIOS DE EXCELÊNCIA EM GESTÃO: EXPERIMENTAÇÃO EM UMA INDÚSTRIA DO SEGMENTO DE MALHARIA - Boas, Gisele Alvim de Rezende Vilas (2009)
This Project aims to present a sample to support the organizational management focusing on the self evaluation based on the criterion of the most important international and national excellence awards in management. The sample had as its objective to allow customized evaluations of performance regarding the management system as well as evaluations of the importance of the practices of management excellence to the company preconized by those awards. The research methodology has been based on a theoretical foundation, comparative analysis of the three main Excellence Awards in Management in Brazil and also based on the experiment of the proposed sample in a knitted fabric textile industry. The proposed sample has allowed a customized evaluation of performance of the management system of the company which has been used as the object of study and the importance of the practices of management excellence involved in the criteria. The contrast between the performance and the importance has allowed the definition of the major organizational aspects aiming the improvement of the company.